THE ROLE OF THE ENGINEERING-GEOLOGICAL AUDIT IN THE QUALITY ASSESSMENT OF THE SURVEYS - V. . Pendin; M. E. Nikulina (Известия высших учебных заведений: Геология и разведка, 2017)
Based on the analysis of the modem quality system of the engineering researches, the authors offer its adjustment by extension with a new procedure - engineering geological audit. In the field of the engineering geology the audit is a principally new method. Studying the fundamentals of the control (checking) procedures allows identifying principal differences between the audit and the control. As a result, the relevance of applying the audit in the engineering and geological practice has been proved. As a result of the study of omission in the modern quality system, a method is proposed to develop mechanism of controlling the methodology of the engineering and geological works. This mechanism will provide the required quality of the researches and its product - engineering and geological information. The comparative analysis of the checking procedures and the audit has shown omissions in quality assessment of the results of engineering and geological investigations. Besides that, this paper summarizes all relevant information developed by he authors earlier.